Investigating the natural history and prognostic factors of ASD in children: the multicEntric Longitudinal study of childrEN with ASD - the ELENA study protocol. Issue 6 (19th June 2019) - Baghdadli, Amaria; Miot, Stéphanie; Rattaz, Cécile; Akbaraly, Tasnime; Geoffray, Marie-Maude; Michelon, Cécile; Loubersac, Julie; Traver, Sabine; Mortamais, Marion; Sonié, Sandrine; Pottelette, Julien; Robel, Laurence; et al.
Abstract : Introduction: There is global concern about the increasing prevalence of autism spectrum disorders (ASDs), which are early-onset and long-lasting disorders. Although ASDs are considered to comprise a unique syndrome, their clinical presentation and outcome vary widely. Large-scale and long-term cohort studies of well-phenotyped samples are needed to better understand the course of ASDs and their determinants. The primary objective of the multicEntric Longitudinal study of childrEN with ASD (ELENA) study is to understand the natural history of ASD in children and identify the risk and prognostic factors that affect their health and development. Methods and analysis: This is a multicentric, longitudinal, prospective, observational cohort in which 1000 children with ASD diagnosed between 2 and 16 years of age will be recruited by 2020 and followed over 6 years. The baseline follow-up starts with the clinical examination to establish the ASD diagnosis. A battery of clinical tools consisting of the Autism Diagnostic Observation Schedule, the revised version of the Autism Diagnostic Interview, measures of intellectual functioning, as well as large-scale behavioural and developmental measurements will allow us to study the heterogeneity of the clinical presentation of ASD subtypes. Subsequent follow-up at 18 months and at 3, 4.5 and 6 years after the baseline examination will allow us to explore the developmental trajectories and variables associated with the severity of ASD. In addition to the children's clinical and developmental examinations, parents are invited to complete self-reported questionnaires concerning perinatal and early postnatal history, congenital anomalies, genetic factors, lifestyle factors, medical and psychiatric comorbidities, and the socioeconomic environment. As of 1 November 2018, a total of 766 participants have been included. Ethics and dissemination: Ethical approval was obtained through the Marseille Mediterranean Ethics Committee (ID RCB: 2014-A01423-44), France. We aim to disseminate the findings through national and international conferences, international peer-reviewed journals, and social media. Trial registration number: NCT02625116 ; Pre-results.